S105 Does adherence to inhaled therapy change following a presentation to the emergency department and a review in asthma clinic?. (December 2018) - Barnard, R; Fernandez, M; Green, L; Roxas, C; Whittock-knott, A; Osman, L; Kavanagh, J; Jackson, DJ; Kent, BD; d'Ancona, GM
Abstract : Introduction: Patients presenting to the emergency department (ED) of a London teaching hospital, with symptoms suggestive of an asthma exacerbation are referred to an asthma clinic for expert review. This study assessed adherence of these patients before and after the presentation, to establish whose suboptimal Inhaled Corticosteroid ±Long Acting Beta2 Agonist (ICS ±LABA) and excessive Short Acting Beta2 Agonist (SABA) use highlighted them as being 'at risk' of unscheduled care. Methods: We reviewed primary care prescription records for patients presenting to the ED who were referred to clinic between July 2017 and June 2018. We assessed records for 6 months pre- and post-ED attendance, and calculated adherence to ICS ±LABA therapy (number of doses issued on prescription/expected number of doses to be used). Patients' ICS/LABA adherence was defined as good if ≥75%, suboptimal if between 50%–74%, and poor if <50%. We calculated SABA usage as puffs/week over the study period. Results: 123 patients' prescriptions were reviewed (age 45.5 (range: 16–86 years); 77.2% female). 107 (87.0%) had a pre-existing diagnosis of asthma. Underuse of maintenance therapy was common prior to ED attendance: only 34.6% of patients appeared to have good adherence; 9% of patients with a clinical diagnosis of asthma had no maintenance therapy prescribed (table 1). ICS/LABA use improved significantly following clinic review, with 63% appearing to have good adherence (p<0.001). High SABA usage was observed both before and after ED attendance, with 21% and 24% of patients using ≥8 puffs of SABA per day respectively (p=0.64). Notably, 20 (16%) patients did not attend clinic follow-up, with 11 of these remaining poorly adherent to maintenance therapy. Conclusions: Most patients were significantly overusing their SABA prior to ED presentation, and this usage did not change. Conversely, ICS ±LABA usage increased significantly, suggesting that the presentation to ED and subsequent review in clinic was successful in educating patients to better adhere to preventer therapy. Unfortunately, over half of those who did not attend clinic follow up are at continued risk of un-scheduled care: general practitioners should be encouraged to review these people as a priority.